FOLKLORE AND ORAL-PROFESSIONAL MUSIC IN THE PIANO WORK OF COMPOSERS OF UZBEKISTAN. POPPY AS A BASIS IN THE WORKS OF COMPOSERS OF UZBEKISTAN AND STYLIZATION OF FOLK MELOS - Azizova Nodira Akmal Kizi (International Engineering Journal For Research & Development, 2021)
The article examines the question of the implementation of the musical heritage of antiquity in the piano work of composers of Uzbekistan, who succeeded in creating piano music based on maqom and folk melos, transmitted orally through the teaching methodology "Teacher-student".